Impact of healthy lifestyle on the risk of type 2 diabetes mellitus in southwest China: A prospective cohort study. Issue 12 (19th September 2022) - Wu, Yanli; He, Xi; Zhou, Jie; Wang, Yiying; Yu, Lisha; Li, Xuejiao; Liu, Tao; Luo, Jianhua
ABSTRACT: Aims: To explore the influence of nine healthy lifestyle factors on the risk of type 2 diabetes mellitus in adults in Guizhou, China. Methods: Data were obtained from a large population‐based prospective cohort study in Guizhou Province, China. A total of 7, 319 participants aged ≥18 years without diabetes at baseline were included in this study and were followed up from 2016 to 2020. A healthy lifestyle score was calculated based on the number of healthy lifestyle factors. Results: During an average of 7.1 person‐years of follow‐up, 764 participants were diagnosed with type 2 diabetes mellitus. Compared with those of participants who scored 0–3 for a healthy lifestyle, the hazard ratios (95% confidence intervals) of those who scored 4, 5, 6, and ≥7 were 0.676 (0.523–0.874), 0.599 (0.464–0.773), 0.512 (0.390–0.673), and 0.393 (0.282–0.550), respectively, showing a gradual downward trend ( P for trend <0.01). More importantly, they had lower fasting and 2 h post‐load plasma glucose levels and fewer changes in plasma glucose levels during follow‐up. If ≥7 healthy lifestyle factors were maintained, 33.8% of incident diabetes cases could have been prevented. Never smoking was the strongest protective factor against type 2 diabetes mellitus. Conclusions: A healthy lifestyle can effectively decrease plasma glucose levels and reduce the incidence of type 2 diabetes mellitus in adults in Guizhou, China. In addition, not smoking may be an effective way to prevent type 2 diabetes mellitus. Abstract : The influence of each healthy lifestyle factor on the risk of Type 2 diabetes mellitus